2003
DOI: 10.1074/jbc.m209682200
|View full text |Cite
|
Sign up to set email alerts
|

CAIR-1/BAG-3 Abrogates Heat Shock Protein-70 Chaperone Complex-mediated Protein Degradation

Abstract: BAG family proteins are regulatory co-chaperones for heat shock protein (Hsp) 70. Hsp70 facilitates the removal of injured proteins by ubiquitin-mediated proteasomal degradation. This process can be driven by geldanamycin, an irreversible blocker of Hsp90. We hypothesize that CAIR-1/BAG-3 inhibits Hsp-mediated proteasomal degradation. Human breast cancer cells were engineered to overexpress either full-length CAIR-1 (FL), which binds Hsp70, or a BAG domain-deletion mutant (dBAG) that cannot bind Hsp70. FL over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
141
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(151 citation statements)
references
References 46 publications
(75 reference statements)
10
141
0
Order By: Relevance
“…In the case of pro-oxidant or aggregation-prone status, BIS has been suggested to interact with HSP70 to activate macroautophagy, whereas interaction of BAG1 with HSP70 is known to be essential for effective proteasomal degradation [16,22]. The misfolding and aggregation of SOD have been shown to increase with oxidative stress in neuronal cells [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of pro-oxidant or aggregation-prone status, BIS has been suggested to interact with HSP70 to activate macroautophagy, whereas interaction of BAG1 with HSP70 is known to be essential for effective proteasomal degradation [16,22]. The misfolding and aggregation of SOD have been shown to increase with oxidative stress in neuronal cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the suppression of BIS expression has been reported to sensitise leukaemic cells to death induced by a glutathionedepriving agent, and the overexpression of BIS attenuates apoptosis induced by the electrophilic 4-hydroxynonenal, suggesting that the induction of BIS could be related to protecting cells exposed to oxidative stress [11,21]. However, the molecular pathway by which BIS modulates cell survival is not well understood, though the binding of BIS to BCL-2 or heat shock 70 kDa protein (HSP70) has provided some insights into this process [10,22]. We recently reported that the downregulation of BIS in C6 glial cells leads to accelerated cell death on oxygen-glucose deprivation (OGD), accompanied by the accumulation of ROS and an impairment in the activation of superoxide dismutase (SOD)1 at the transcriptional level [23].…”
Section: Introductionmentioning
confidence: 99%
“…19 It is likely that the Hsp70-mediated delivery of other anti-apoptotic proteins to proteasome could be influenced by BAG3 as well. 23 In addition, BAG3 can also bind to other proteins via its proline-rich (PXXP) or WW domains, 24 possibly resulting in a modulation of their activity. Because of its multifaceted ability to complex with many proteins, BAG3 can regulate factors that are particularly relevant in the context of specific tumour types, such as BAX in glioblastoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the BAG3/Hsp70 complex has recently been shown to participate in the proteasome -mediated degradation of intracellular proteins. 21 It is therefore likely that BAG3 protein can influence the activity of more than one factor involved in the apoptotic Effect of BAG3-specific antisense oligodeoxynucleotides on BAG3 protein levels in U937 cells. U937 cells were plated at a density of 5 Â 10 5 /ml and cultured for 15 h without or with DEM (Sigma, St Louis, MO, USA) (1.2 mM) and/or BAG3 antisense or control nonsense phosphorothioate ODN 16 (5 mM).…”
Section: Bag3 Protein Regulates Stress-induced Apoptosis In Normal Anmentioning
confidence: 99%